Research-Oriented Collaborative Inquiry Learning (REORCILEA) Model: Improvement of Students' Critical Thinking Ability and Collaborative Skills in Thermochemistry of Materials - Titis Wulandari; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
This quantitative quasi-experimental study with a posttest-only control group design aimed to analyze differences in critical thinking ability and collaborative skills between students using a research-oriented collaborative inquiry learning model and those using a scientific approach in thermochemistry materials. Conducted with four classes XI MIA students in Pekanbaru, divided into experimental and control groups, the study used essay tests and observation sheets as instruments, with data analyzed via MANOVA. The research findings indicate that: (1) there are differences in critical thinking ability and collaborative skills between students using the research-oriented collaborative inquiry learning model and students using the scientific approach in thermodynamics material; (2) there is a difference in critical thinking ability between students who followed the research-oriented collaborative inquiry learning model and students who followed the scientific approach in thermodynamics material; (3) there is a difference in collaborative skills between students who followed the research-oriented collaborative inquiry learning model and students who followed the scientific approach in thermochemistry material.